2021
DOI: 10.1016/j.ejvs.2021.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Endoleak With or Without Intervention and Survival After Endovascular Aneurysm Repair

Abstract: WHAT THIS PAPER ADDSA type 2 endoleak (T2EL) following endovascular aneurysm repair (EVAR) is associated with an increased need for secondary intervention and presumed risk of rupture, thus analysing the impact of an isolated T2EL on mortality is necessary. After an 11 year follow up, survival in patients who underwent a secondary intervention for T2EL was not better than those who were treated conservatively. Most importantly, this study highlights the need for a conservative approach and for high quality pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 31 publications
2
13
5
Order By: Relevance
“…Endoleak following EVAR was less common in the present research (6.7 percent) than it had been in previous studies (12 percent) [19]. The most common reason for subsequent intervention is an endoleak [20]. Endoleaks following open surgery are uncommon, although one has been documented [21].…”
contrasting
confidence: 45%
“…Endoleak following EVAR was less common in the present research (6.7 percent) than it had been in previous studies (12 percent) [19]. The most common reason for subsequent intervention is an endoleak [20]. Endoleaks following open surgery are uncommon, although one has been documented [21].…”
contrasting
confidence: 45%
“…Recently published data from our research group compared patients with and without a type II endoleak, which showed that overall survival was unaffected by the presence of a type II endoleak (p=0.537). 16 However, this type II endoleak study included patients with and without abnormalities at their initial CTA, therefore, the results are not directly comparable. Baderkhan et al 11 also demonstrated no difference in overall survival in patients classified as high (sealing zone less than 10 mm and/or presence of an endoleak) and low risk on the first postoperative CTA of adverse events after EVAR (log rank; p=0.077).…”
Section: Discussionmentioning
confidence: 93%
“…30 However, in the Netherlands the majority of the imaging follow-up is performed with ultrasound. 31 Health care providers must be aware of the difference in anxiety levels and the associated imaging modalities.…”
Section: Discussionmentioning
confidence: 99%